Which One Has The Greater Influence On The Green Purchase Decision? - Dewi Rakhmawati; Okshanela Okshanela (Jambura Science of Management, 2023)
Purpose: This study aims to analyze the effect of lifestyle variables and trust variables on green purchase decisions in buying organic vegetables in Malang City.Design/Methodology/Approach: This research was conducted using a descriptive quantitative method, and the technique employed was multiple linear regression with the assistance of IBM SPSS software version 25. The study utilized 100 questionnaires administered to a sample of individuals who have made purchases of organic vegetables in the Malang city area. The sample was selected using non-probability sampling.Findings: The green lifestyle variable in this study has a significantly positive effect on the green purchase decision of organic vegetable products. It is also known that the green trust variable has a significant positive effect on the green purchase decision as well. While the two variables, green lifestyle and green trust, are carried out simultaneously, they also have a positive and significant influence on green purchase decisions in purchasing organic vegetable products in Malang City.